Deciphering Assorted Findings on Marketer Transgression Linked to Service Recovery Paradox - Banerjee, Padmakali; Banerjee, Prabuddha (Indian Journal of Marketing, 2012)
It has been of great importance both to academicians and practitioners to home in on the factors that constitute service failure. Though the need of the hour for the service providers is to provide efficient and defect-free services, it is almost diabolical that customers need to be nudged to complain. Service Recovery Paradox (SRP) refers to a seemingly illogical situation where - following a failure/recovery process - higher levels of customer satisfaction are achieved than in the case of customers who have not experienced any service failure. The goal of this research is built upon contemporary and current understanding by investigating the SRP using a string of published reports.